Minty lemma for inverted vector variational inequalities. (4th March 2017) - Lee, B. S.; Salahuddin,
Abstract: In this paper, we introduce Stampacchia-type inverted vector variational inequalities and Minty-type inverted vector variational inequalities and discuss Minty lemma for the inequalities showing the existence of solutions to them in Banach spaces. Next, we consider the equivalence of our Minty lemma with Brouwer's fixed point theorem as an application.